Embedding the local sociocultural in Indonesia for English writing skill - Prasetyo, Dodi Erwin (Jurnal Pendidikan Bahasa dan Sastra, 2021)
The writing skill and sociocultural cannot be separated. Many previous study had been conducted to analyze the sociocultural and the writing skill. However, most of them were in foreign country. It is extremely still rare undertaking the study of local sociocultural in Indonesia which was integrated with English writing skill. Therefore, this paper aimed at exploring and discussing the integrations between the local sociocultural in Indonesia and English writing skill. This paper applied a library research method by obtaining data through reseach articles, journal, book and so forth. It presented the overviews of sociocultural and writing skill, the delineations of sociocultural in the pedagogical aspect, the sociocultural paradigms in Indonesia context, pedagogy challenge toward the use of local sociocultural in Indonesia for writing, and integrating the local sociocultural and English writing skill. The steps of integrations between the local sociocultural and English writing skill are that (1) instructors teachs what their social values (attitude, norms, moral, etc) and what their cultural delineations (traditions, arts, historical building, etc) to learners, (2) the writing strategy is taught by instructors in terms of planning, drafting, editing and final product, (3) instructors reqiure students to write their own written text. The virtual media can be utilized at all of those steps. Further discussion in the future is needed among experts in education, linguist and curriculum maker to design and achieve the fruitful goals.